SUSTAINABILITY, ADAPTABILITY, INTEGRATION AS NEW CONCEPTS OF ENERGY DEVELOPMENT - Дзьоба, Олег Григорович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The purpose of the article is to identify and systematize key concepts of energy development in conditions of increased turbulence and European integration processes, to form the foundations of energy system transformation and to create a theoretical basis for the development of relevant models based on the introduction of new mechanisms for implementing the structural components of the concepts of sustainability, adaptability and integration. The main emphasis is placed on studying the state of the global energy sector and the energy sector of Ukraine from the perspectives of sustainability, decarbonization, digitalization, energy security, and other important conceptual paradigms of today. The research is based on the fundamental principles of economic theory and management science, the works of leading domestic and foreign specialists, the study of modern trends in the development of the energy industry and the conceptual principles of managing transformation processes in the context of sustainable development. The importance and necessity of improving the conceptual foundations of the transformation and development of energy systems of various hierarchical levels are proven and relevant strategic concepts for energy development, such as sustainability, adaptability, and integration, are proposed. The structure and individual components of the above strategic concepts are revealed and analyzed, as well as the mechanisms for their practical implementation are substantiated. An improved 4D+I concept (Decarbonization, Decentralization, Digitalization, Diversification, Integration) is proposed as the basis for developing strategic plans for the development of energy systems at the industry level. The issues of the article are relevant and focused on solving the problems of energy security, decarbonization, environmental sustainability, political, regulatory and technological resilience by improving the effective use of important strategic guidelines for transformational transformations of energy systems.